2018
DOI: 10.1016/j.earscirev.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The multidisciplinary origin of soil geography: A review

Abstract: Soil geography should be clearly recognized as a sub-discipline of physical geography and soil science, but at various times over the last century it was accepted as a complementary and descriptive sub-discipline of botany, agronomy and geology. In other words, there was not a clear consensus about its definition and origins. The main goal of this paper is to conduct a historical review (s. XX-XXI) of soil geography to clarify its origin, early methods, first authors and the importance of its interdisciplinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 84 publications
2
54
0
1
Order By: Relevance
“…This mechanical impact resulted in high erosion rates such as we found in Les Alcusses Valley. We found that the young vineyards produced higher amounts of sediment as soils were compacted and bare, and had low roughness (Rodrigo‐Comino et al ., ). During this time, rainfall events caused large amounts of sediment to be transported from the upper parts of the hillslope to the lower parts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This mechanical impact resulted in high erosion rates such as we found in Les Alcusses Valley. We found that the young vineyards produced higher amounts of sediment as soils were compacted and bare, and had low roughness (Rodrigo‐Comino et al ., ). During this time, rainfall events caused large amounts of sediment to be transported from the upper parts of the hillslope to the lower parts.…”
Section: Discussionmentioning
confidence: 97%
“…Soil erosion shapes the Earth's landforms, and in turn landforms determine soil erosion rates and pedogenesis (García‐Ruiz et al ., ; Martínez‐Murillo et al ., ; Zeraatpisheh et al ., ). Biota, especially plants (Swanson et al ., ; Kirkby, ; Bochet et al ., ) and human activities have a strong influence on this interaction as they determine processes and their rates (Dotterweich, ; Rodrigo‐Comino et al ., ), and also affects the soil quality (Khaledian et al ., , b; Keshavarzi et al ., ). Similarly, landforms are a result of the long‐term connectivity dynamics resulting from the complex interactions between water and sediment fluxes, slope angle, altitude, rock exposure, climate, stratification and parent material (Bracken and Croke, ; López‐Vicente et al ., ; Parsons et al ., ), while landforms also determine connectivity and erosion rates due to the effect of slope angles and position in landscapes (Fox et al ., ; Nadal‐Romero et al ., ; Taguas et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Future research may allow a better understanding of spatial regimes of wildfires contributing to a more effective management of fragile areas. Further studies should specifically focus on intrinsic changes in the carbon cycle [93], the role of soils in the earth cycles [94] and the soil erosion cycle [95]. Additionally, most research carried out on forest fires has investigated plant composition, soil properties, soil erosion and runoff generation, and the restoration of soil and vegetation cover after fire [96][97][98][99][100][101].…”
Section: Discussionmentioning
confidence: 99%
“…To resolve this, we presented a pedo-geomorphological approach to distinguish different management zones and discretize soil micronutrients in order to fill the gaps in land degradation neutrality plans, which should be designed in Iran and used as soon as possible. After finishing this research, we want to highlight that a proper delineation of site-specific management zones should be considered in Iranian agricultural and forest land management strategies affected by potential or real degraded areas, which are tasks traditionally related to the soil geographers, biogeographers and geomorphologists [79,80]. However, now we state that there is a necessity for the development of prospective tools in management plans to correctly achieve land degradation neutrality coinciding with other authors [29,65], but always involving the whole scientific community, stakeholders and policymakers [81,82].…”
Section: Discussionmentioning
confidence: 99%